STUDI METAANALISIS TENTANG HUBUNGAN ANTARA LINGKUNGAN BELAJAR TERHADAP SIKAP BELAJAR - NDOLUANAK, YOFRAN HENGKI; Riyadi, Riyadi; Sarifah, Iva (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2023)
ABSTRACT This research aims to examine the results of previous research related to the learning environment and learning attitudes using a meta-analysis study approach. Based on the results of the analysis that has been carried out, it is known that the actual correlation results have an average of 0.676 and a Standard Deviation of 0.1220. And because the average correlation coefficient of the 3 studies is greater than 0, it can be concluded that from this meta-analysis study there is a positive influence of the learning environment on students' learning attitudes. This means that a good work environment can make learning attitudes more positive. Keywords: Learning environment, Learning Attitudes, Correlation Test, Metaanalysis